Ethanol extract of red fruit (Pandanus conoideus lam.) improved lipid profile of dyslipidemic-male wistar rats (Rattus norvegicus) - Sriwiyanti Sriwiyanti; I Gusti Made Aman; Gde Ngurah Indraguna Pinatih (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2021)
Introduction: Dyslipidemia is one of aging- related disease associated with unhealthy food such as high calories and fat. Pandanus Conoideus Lam. with high antioxidant capacity might ameliorates dyslipidemia phenotypes. This study aimed to prove that ethanol extract of red fruit improves lipid profiles of dyslipidemic-rats (Rattus norvegicus). Methods: This was an experimental study with a pretest-posttest control group design, using 14 wistar rats males. Rats were then divided into 2 groups (n= 7). The first group was treated with aquabidestilata 1 mL for 30 days (P0). The second group was treated with extract of red fruit ethanol of 168 mg/200 gr BW for 30 days (P1). Results: The control group (P0) treated with aquabidestilata, total cholesterol levels increased into 221.48 ± 3.64 mg/dl (p <0.05), triglyceride levels elevated into 132.92±3.01 mg/dl (p <0.05), HDL levels depleted into 22.83 ± 2.26 mg/dl (p <0.05), and LDL levels was increased from 76.77 ± 3.33 mg / dl to 78.63 ± 2.84 mg / dl (p <0.05). In contrast, the red fruit ethanol extract in treatment group (P1) experienced decrease on total cholesterol level into 118.41 ± 2.15 mg/dl (p <0.05), triglyceride levels into 91.81 ± 2.71 mg/dl (p <0.05), and LDL levels into 45.85 ± 2.59 mg/dl (p <0.05), and elevation on HDL levels from 25.77 ± 1.36 mg/dl to 55.76 ± 2.35 mg/dl (p <0.05). Conclusion: This study indicated that administration of ethanol extract of red fruit (Pandanus conoideus lam.) improved lipid profiles of dyslipidemic-rats (Rattus norvegicus).